Sous-titrage et apprentissage des langues - Gambier, Yves (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Our overview on subtitling and language learning is based on a fact and a question. The internationalisation of media and the development of Communication and Information technology (ICT) is bound to change our relationship to languages. But how can we improve our command of foreign languages? Memories and experiences of the classroom are not always positive. On the other hand, in today's world, we cannot avoid reading on screens. Since the beginning of the 1980 ’s, several studies have been carried out on the possible use of intralingual subtitles for language acquisition. We first review the types of studies and the scope of some of them, before considering specific empirical studies dealing with different language competences (vocabulary, listening comprehension, language transfer). Finally, we suggest new research topics, regarding the use of subtitling in natural and institutional language learning settings.